(untitled) (Innovative professional education, 2025)
The article presents the results of the literature analysis regarding the economic training of future professional junior bachelors in the organization and technology of farming. Based on the rules of formal logic, the concept of «economic competence of the future professional junior bachelor in the organization and technology of farming» is interpreted. Based on the analysis of the content characteristics of the phenomenon, it is proposed to consider the economic competence of these specialists as a unity of the following mutually determined components: motivational-value, cognitive, activity and personal-reflective